Microbiota, parasitic infections and their relationship with nutritional status and neurocognitive functioning in children from Ecuador—Proyecto Guagua: research protocol for a cross-sectional study - Abril-Ulloa, Sandra Victoria; Carpio-Arias, Tannia Valeria; Alvarado-Barba, Renata Alejandra; Ríos-Romero, Cristina Gabriela; Vinueza-Veloz, Pamela; Lima-dos-Santos, Sueny Paloma; Astudillo-Skliarova, Igor Eduardo; Arias-Gutiérrez, Ruth Irene; Pérez-Quintana, Manuel; Boele, Henk-Jan; Vinueza-Veloz, María Fernanda (Frontiers in Public Health, 2025)
IntroductionThis protocol outlines the Proyecto Guagua, which aims to explore the relationship between the characteristics of the gut microbiota, parasitic infections, nutritional status, and neurocognitive functioning in school-age children in Ecuador.Methods and analysisProyecto Guagua is a cross-sectional observational study funded by the Escuela Superior Politécnica de Chimborazo. It is being carried out in several counties across different geographical regions in Ecuador, including Galápagos. The study targets children regularly attending school, aged 6–12. We aim to recruit 450 children, with data already collected from nearly 300 participants (67%). Enrolled children undergo comprehensive evaluations assessing nutritional status, body composition, motor learning, social skills, cognitive ability, sleep habits, and physical activity. Caretakers and school teachers are interviewed regarding hygiene, eating habits, and food handling. Stool samples are collected to analyze the gut microbiota and determine the presence of parasites. In the analysis phase, we aim to describe differences in microbiota population structure and diversity among undernourished and obese/overweight children, and children with parasitosis compared to their peers. We also plan to test the hypothesis that an altered microbiota mediates the influence of malnutrition on neurocognitive functioning and parasitosis.Ethics and disseminationProyecto Guagua received ethical approval from the Ethics Committee of Universidad de Cuenca in July 2022. Following the pilot phase, an addendum and minor changes to the study design were approved in October 2022. Written consent was obtained from parents before enrolling their children in the study. Parents and children were informed of their right to withdraw from the study at any time. The findings of “Proyecto Guagua” will be disseminated through open-access, peer-reviewed publications and presented at local and international scientific events.